Pedagogy of feminist hope: Findings from teaching portuguese language and literature (Revista Contexto & Educação, 2025)
This article analyzes a feminist and anti-racist pedagogical experience carried out in 9th-grade Portuguese Language and Literature classes at a municipal school in Canoas, RS, Brazil. Drawing on critical feminist epistemology and language education based on discursive genres and Bakhtin's dialogical concept of language, it seeks to highlight the political resistance inherent in teaching practices. This is explored through the idea of a pedagogy of feminist hope, which interweaves Paulo Freire's insights with intersectional feminist perspectives, understanding education as a tool for citizenship engagement and confronting inequalities. Among the findings, the study emphasizes the potential for creating learning communities through seminars focused on the artistic and cultural production of Black women from feminist viewpoints. Within these communities, it was observed that safe spaces for demonstrating vulnerabilities, shared and democratic knowledge construction, and critical social awareness among students developed. We also underscore the relevance of these seminars as a practice in mother tongue and literature teaching, as they facilitate the sharing of readings that connect words to lived experiences, challenging traditional hegemonic curricula and fostering critical thinking by questioning inequalities and envisioning possible futures.
Keywords: Pedagogy of Feminist Hope; Literature and Portuguese Language Teaching; Critical Education